Exploration of different x-ray Talbot-Lau setups for dark-field lung imaging examined in a porcine lung - Ludwig, Veronika; Seifert, Maria; Hauke, Christian; Hellbach, Katharina; Horn, Florian; Pelzer, Georg; Radicke, Marcus; Rieger, Jens; Sutter, Sven-Martin; Michel, Thilo; Anton, Gisela (Physics in Medicine and Biology, 2019)
X-ray dark-field imaging is a promising technique for lung diagnosis. Due to the alveolar structure of lung tissue, a higher contrast is obtained by the dark-field image compared to the attenuation image. Animal studies indicate an enhancement regarding the detection of lung diseases in early stages. In this publication, we focus on the influence of different Talbot-Lau interferometer specifications while maintaining the x-ray source, sample magnification and detector system. By imaging the same porcine lung with three different grating sets, we analyze the contrast-to-noise ratio of the obtained dark-field images with respect to visibility and correlation length. We demonstrate that relatively large grating periods of the phase and of the analyzer grating are sufficient for high quality lung imaging at reasonable dose levels.
CRIS-Team WoS Importer:2019-03-29